The Campi Flegrei Deep Drilling Project - Marco Sacchi (Scientific Drilling, 2007)
A workshop on the ‘Campi Flegrei Deep Drilling Project’ was held on 13–15 November 2006 in Naples, Italy, in a location within the Campi Flegrei caldera and close to the main candidate site for on-landdrilling—the Bagnoli area (Fig. 1). The workshop was among the first European efforts to assess volcanic hazard within the context of the Integrated Ocean Drilling Program (IODP) and the International Continental Scientific Drilling Program (ICDP). The participants presented evidence that the setting and features of the partially submerged Campi Flegrei Caldera provides an ideal natural laboratory for future joint ICDP-IODP research. About seventy scientists from nine countries representing multidisciplinary fields participated in the meeting. A plenary session was held on the fififirst day, followed by groups for onland and off-shore drilling working separately during the second and third days to define science targetsand appropriate tools for an integrated amphibious drilling program. Important on-going ICDP and IODP drilling projects in areas with objectives and technologies of interest to the Campi Flegrei projectwere presented during joint sessions.